Nuclear factor erythroid 2-related factor 2 as a treatment target of kidney diseases. Issue 1 (January 2020) - Ito, Marie; Tanaka, Tetsuhiro; Nangaku, Masaomi
Abstract : Purpose of review: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor which regulates a wider range of downstream pathways than previously thought. This review focuses on the novel findings about the internal regulatory mechanisms of Nrf2, the expanding understanding of its role in maintaining cellular homeostasis and the attempts to broaden the clinical application of its activators. Recent findings: Nrf2 is in charge of the maintenance of cellular homeostasis under stress and there exist the internal regulatory mechanisms for Nrf2 which have recently been elucidated. New downstream pathways of Nrf2 have been discovered, including the defense against ferroptosis, the latest concept of cell death. Several Nrf2 activators are at various stages of clinical development and are being tested in clinical trials for chronic kidney disease (CKD) including diabetic kidney disease, Alport syndrome, autosomal dominant polycystic kidney disease and focal segmental glomerulosclerosis. Summary: Nrf2 has been gathering attention as an emerging treatment target of chronic diseases which have oxidative stress and inflammation as their pathogenesis including CKD. Basic and clinical studies are under way to establish its role as a target for treatment of those diseases.